History of the Development of Ahmadiyya Islam: Case Study Indonesia Starting in the 20th century - Suhadak, Totok (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the history of the development of Ahmadiyah Islam in Jambi Province and the factors that influenced its spread. Ahmadiyah Islam, founded by Mirza Ghulam Ahmad in India in the late 19th century, began to enter Indonesia in the early 20th century and spread to various countries, including Indonesia. Through a historical approach, this study explores written and oral sources to understand the process of Ahmadiyah's entry into Indonesia, the community's response to this sect, and the challenges faced by the Ahmadiyah community in the region. In this study, historical research methods were used, including heuristics, source criticism, interpretation, and synthesis to compile a narrative of the development of Ahmadiyah in Indonesia. The results of the study show that the Ahmadiyah community in Indonesia developed through trade routes and close social relations with centers of da'wah in Indonesia, despite facing challenges from mainstream Islamic groups that reject their teachings. This study also reveals the social and political dynamics that influence the existence of Ahmadiyah in Jambi, both in the context of the internal community and local government policies related to religious freedom. This study is expected to contribute to the understanding of the diversity of sects in Islam in Indonesia